Improvement of a Circular Microstrip Antenna Excited by Four Feeds and Suspended with Artificial Magnetic Conductors - Sanchai Eardprab; Chuwong Phongcharoenpanich; Danai Torrungrueng (My University, 2013)
The proposed antenna is a circular microstrip structure excited by four feeds and suspended with artificial magnetic conductors (AMCs). The multifeed circular microstrip antennas can generate a high circularly polarized performance by using a different feed arrangement. AMC structures with a square, circular, or octagonal patch on a unit cell are designed and applied to circular microstrip patch antennas for the enhancement of antenna performance. It is found that simulated results of the proposed antenna are well suited. The properties of wide beamwidth with good axial ratio can be achieved when applying the proposed AMC structures to circular microstrip antennas. The antenna prototype was fabricated to validate simulated results.
Keywords: Beamwidth; Patch antenna; Axial ratio; Advanced Antenna and Metasurface Technologies